Sepak Bola sebagai Simbol Bangsa: Analisis Identitas Nasional dalam Aktivitas Timnas Indonesia - Fawaid, Ahmad (Maliki Interdisciplinary Journal, 2025)
The Indonesian national football team as a national identity that can unite various races, tribes, and religions in Indonesia. The Indonesian national team is also a source of pride for the Indonesian people. In addition, the Indonesian national team has an important role in showing national identity. This article will discuss how symbols, rituals, and activities related to the Indonesian national team reflect national identity, national values ​​and strengthen the sense of nationalism among the community. The type of research method used in this article is Literature. This study analyzes the use of national identity in activities carried out by the Indonesian national team.